IPTEKS BAGI MASYARAKAT KELOMPOK TANI TERNAK KERBAU - Cahya Setya Utama; B. Sulistiyanto; Sri Sumarsih (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2014)
The objective of this program was to increase skills and improve maintenance management and animal feed’s buffalo processing. In general, the activities of science and technology in the community of buffaloes in farmer groups successful and able to motivate and invigorate the spirit to grow and progress through the efforts of buffaloes. Indicators of program success was shown by the ability of farmer groups in the mastery of theory, techniques, skills and management of complete feed production, fermentation feed, compost and liquid fertilizer and maintenance management buffaloes. Participants were expected ready to be a candidate new entrepreneurs and be able to make a simple business planning. The participants seen work well in the mastery of theory and practice with the composition of 25% and 75%.